Penggunaan Artificial Intelligence (AI) Dalam Penentuan Arah Kiblat - Hamas, Nuril Fathoni; Andri, Sela Septi (ELFALAKY: Jurnal Ilmu Falak, 2025)
Facing the Qibla is one of the prerequisites for valid prayer. The methods of determining the Qibla direction have been extensively explored, ranging from simple methods to using highly advanced technology. The emergence of Artificial Intelligence (AI) technology, which is currently evolving, is designed to address various issues, including the Qibla direction. One of the evolving models is Natural Language Processing (NLP), which enables computers to understand human natural language. Even when given questions about the Qibla direction of a place, AI can respond with the azimuth value according to the desired city input by the user. The aim of this paper is to examine how the use of artificial intelligence (AI) in determining the Qibla direction, and to determine the accuracy of the Qibla direction produced by Artificial Intelligence. The method used in this research is a qualitative method with an experimental approach, which is used to investigate the influence of certain treatments on others under controlled conditions. In this case, primary data sources are taken from artificial intelligence given keywords (prompts) to obtain the Qibla direction of a city. Then, the results of the Qibla direction from the artificial intelligence machine (AI) are analyzed based on fiqh (Islamic jurisprudence) and astronomical principles. The results of this study indicate that there is artificial intelligence that produces accurate calculations of the direction of the Qibla, namely ChatGPT, while others are still not completely accurate because the answers produced by the artificial intelligence have not applied mathematical principles in their calculations so that they cannot be relied on as a guideline in determining the direction of the Qibla. Therefore, further development is needed in the use of artificial intelligence (AI) in determining the direction of the Qibla.